2021
DOI: 10.1186/s13102-021-00350-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of personal activity intelligence (PAI) monitoring in the maintenance phase of cardiac rehabilitation: a mixed methods evaluation

Abstract: Background Personal activity intelligence (PAI) is a single physical activity metric based upon heart rate responses to physical activity. Maintaining 100 PAI/week is associated with a 25% risk reduction in cardiovascular disease mortality and 50 PAI/week provides 60% of the benefits. The effect of utilising this metric within a cardiac population has not been previously investigated. The aim of this study was to determine the effect of PAI monitoring on the amount and/or intensity of physical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
16
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 47 publications
(54 reference statements)
4
16
2
Order By: Relevance
“…We recently conducted a single-arm trial using the PAI metric for PA self-monitoring in cardiac rehabilitation patients (9). Participants wore a smartwatch that collected PAI data, which they were blinded to for the first 3 wk, and could see during the next 3 wk.…”
mentioning
confidence: 99%
“…We recently conducted a single-arm trial using the PAI metric for PA self-monitoring in cardiac rehabilitation patients (9). Participants wore a smartwatch that collected PAI data, which they were blinded to for the first 3 wk, and could see during the next 3 wk.…”
mentioning
confidence: 99%
“…PAI can provide readily available and quantifiable feedback on an individual's PA level which in turn could serve as an important tool in health management among clinicians and the patients they serve. Keeping with that, in an exploratory study conducted in conjunction with cardiac rehabilitation in Australia, the use of PAI, incorporated in an App and a wearable heart rate monitor, served as a motivator for PA. 29 Cardiac patients who used PAI during the last 3 weeks of a 6-week intervention were found to be more physically active than those not using PAI. 29 Others demonstrated that individuals with type 2 diabetes using PAI (PAI-App and wearable heart rate monitor) over 12 weeks significantly increased their exercise capacity and sleep time, and decreased body fat percentage and sex-specific adiposity when compared with their peers following contemporary PA recommendations.…”
Section: Discussionmentioning
confidence: 94%
“…Keeping with that, in an exploratory study conducted in conjunction with cardiac rehabilitation in Australia, the use of PAI, incorporated in an App and a wearable heart rate monitor, served as a motivator for PA. 29 Cardiac patients who used PAI during the last 3 weeks of a 6-week intervention were found to be more physically active than those not using PAI. 29 Others demonstrated that individuals with type 2 diabetes using PAI (PAI-App and wearable heart rate monitor) over 12 weeks significantly increased their exercise capacity and sleep time, and decreased body fat percentage and sex-specific adiposity when compared with their peers following contemporary PA recommendations. 16 The introduction of PAI in everyday life has the potential to turn a theoretical association of PA into a daily encouraging process through monitoring and challenging the device-wearer to achieve a practical goal every day.…”
Section: Discussionmentioning
confidence: 94%
“…Recent studies using objective measurements of PAI through a wearable heart rate monitor and mobile app have shown that individuals with type 2 diabetes using PAI significantly improved their exercise capacity and sleep time when compared with the control group following current PA recommendations [ 41 ]. Similarly, the monitoring of PAI scores was associated with an increase in PA among cardiac patients compared with those not using PAI [ 42 ]. The advantages of PAI may be partially attributed to the personalized metric it provides based on the individual heart rate response to exercise, which provides a readily available index of exercise intensity and energy expenditure.…”
Section: Discussionmentioning
confidence: 99%
“…However, this kind of research is more feasible now than ever largely because of the increased popularity and accessibility of activity-based wearables including accelerometers and should be a goal for future studies. The PAI studies using objective measurements in individuals with diabetes and cardiac patients have shown that the use of PAI is feasible, acceptable and efficacious, and the majority of participants reported increased motivation to exercise and to continue to use PAI long-term [ 41 , 42 ]. Nevertheless, future prospective cohort studies using the objective measurements of PAI are warranted and would help to enhance our understanding of the utility of the PAI score in disease prevention and management.…”
Section: Discussionmentioning
confidence: 99%